Molecular discrimination of shelf-spawned eggs of two co-occurring Trachurus spp. (Carangidae) in southeastern Australia: a key step to future egg-based biomass estimates. (11th September 2014) - Neira, Francisco J.; Perry, Robert A.; Burridge, Christopher P.; Lyle, Jeremy M.; Keane, John P.
Abstract: A molecular approach was successfully developed to discriminate between spawned eggs of the pelagic carangids Trachurus declivis and Trachurus novaezelandiae collected during ichthyoplankton surveys conducted in October 2002 and 2003 along shelf waters of Queensland (Qld) and New South Wales (NSW), in southeastern Australia (25 o 50′–37 o 30′S). Visually identified Trachurus eggs were subjected to mtDNA analysis by targeting specific fragments of the cytochrome oxidase subunit 1 ( CO1 ) and cytochrome b ( Cyt b ) genes, with three diagnostic sites (single-nucleotide polymorphisms) within a 297 bp segment of Cyt b (558, 588, 825) providing the best approach to discriminate between species. Polymerase chain reaction amplification and sequencing of 608 suspected Trachurus eggs resulted in 586 (96.4%) high-quality sequences that unequivocally identified 315 and 207 eggs as T. declivis and T. novaezelandiae, respectively, as well as 18 "variant haplotype" eggs that exhibited a base substitution at one of the diagnostic sites; the remaining 46 sequences aligned to three different genera in GenBank including two carangids, thus highlighting the effectiveness of molecular methods for egg identification. Rehydrated, mtDNA-verified eggs of T. declivis were significantly larger (0.97 ± 0.01 mm) than those of T. novaezelandiae (0.82 ± 0.01 mm), though still proved problematic to identify to species when relying on morphology alone. Egg distributions showed main spawning areas of T. declivis and T. novaezelandiae confined mostly to southern NSW (>32°S) and northern NSW/southern Qld (<32°S), respectively, with T. novaezelandiae likely to continue spawning further south during summer with the gradual temperature increase associated with the south-flowing East Australian Current. Overall findings support the adoption of comparable molecular protocols to verify identification of wild spawned eggs to species level, especially eggs collected during the application of the daily egg production method to estimate spawning biomass of pelagic species, as well as biological fish studies.